Comparative Sociometric Profile Of Regular Alcohol Drinking Adolescents - Georgi Sarov (Journal of Biomedical & Clinical Research)
Jacob Moreno defined sociometry as “the inquiry into the evolution and organization of groups and the position of individuals within them”. Every person composes their own group of significant others and the social relations in this dominated by the person group of the most important people in their life is called sociometric profile. The sociometric profile provides an opportunity to reveal social bonds, dependences and influences that impact one's behavior. The aim of the study was to describe the sociometric profile of regularly drinking adolescents as a result from comparison with the sociometric profile of non-drinking adolescents. We conducted a survey among 903 students (aged 15-19), by means of a self-administered questionnaire about relations with father, mother, friends and lovers. Of these, 169 identified themselves as regular drinkers (RDAs) and 279 ‒ as abstainers (NDAs). We compared these groups to reveal the comparative sociometric profile of drinking adolescents. It was found that RDAs were significantly more likely to be: 1) highly dependent on their lovers (OR=1.6); 2) detached from their mothers (OR=4.55); 3) in ambivalent relations with their friends; 4) without significant differences in relations with their fathers. It seems that the Stars of RDAs are their lovers, the Isolates are their mothers and friends are their ambivalent Mutual Choice. This comparative sociogram suggests that lovers are likely to be the most influencing person among RDAs' significant others and intimate relations might be the main target in alcohol prevention programs.